Estudo ecogeográfico, fenologia, crescimento e produção de Lippia lasiocalycina Cham. (Verbenaceae) - Rocha, Maria Clara de Almeida Lima (2025)
Lippia lasiocalycina Cham. is native to Brazil and occurs in all regions of the country. It hashighbioactive potential, mainly as a fungicide and insecticide. However, it lacks ecogeographic,phenological and cultivation studies, which are essential for its domestication, conservationandinsertion in the market. Thus, this study evaluated its ecogeography and the effect of seasonalityon phenology, growth and essential oil production. The locations where the species occurredwere characterized, and the research was carried out at the Horto Florestal Experimental Unit ofthe State University of Feira de Santana. The plants were grown in the field for phenological,growth and production monitoring, and climate data were obtained fromspecializedplatforms.The species occurs throughout Brazil, mainly in the Northeast, Central-West and Southeast, witha preference for dystrophic soils, the Cerrado biome, tropical climate, well-drained RedLatosolsoils, with low fertility and acidic pH. It presented high phenological synchrony, withconstantmature leaves. Fruiting was seasonal and negatively correlated with precipitation. Leaf fallincreased with radiation, temperature and photoperiod, but decreased with precipitationandhumidity, unlike senescence. Height decreased with higher radiation and temperature; stemdrymass, its diameter and total dry mass decreased with precipitation, while the number of tillersincreased. Total leaf area was lower in longer photoperiods, and higher with humidity. Essentialoil production remained stable. Thus, Lippia lasiocalycina Cham. adapts well to cultivation, andthese findings favor its management, conservation and sustainable commercial exploitation